Sources of Momentum Profits in Emerging Stock Markets: The Case of Dhaka Stock Exchange - Hossan, Mohammad Akter; Park, Sang-Bum (Indian Journal of Finance, 2013)
This study focuses on sources of momentum strategies for the Dhaka Stock Exchange of Bangladesh. For these purposes, this study applies models based on serial correlation and lead - lag effect suggested by Jegadeesh and Titman (1993) and (1995) respectively. Results of these models find that investors' overreaction to firm- specific information is the source of momentum profits in the Dhaka Stock Exchange. Furthermore, lead- lag pattern in stock returns does not contribute to the expected momentum profits in Dhaka Stock Exchange. However, this study finds a large difference between expected and actual momentum profits for the Dhaka Stock Exchange.